Market analysis to facilitate expansion of wholesale wine sales and distribution of G Winery - Espinda, Megan (Kansas State University, 2021)
The wine industry in Ohio is thriving and has been a major financial contributor to the economy throughout the last decade. The objective of this research is to conduct a market analysis and develop a business expansion plan for G Winery to further its market share within the wine wholesale and self-distribution segment. The results will also inform decisions to create a new position for a Wholesale Account Specialist. The research insights will facilitate planning and decision making in G Winery to support its growing interest of expanding wholesale wine marketing and distribution within Ohio. This study analyzes G Winery’s current business model and provide insights on strategic marketing opportunities, product values, and the internal processes of offering the strongest value proposition for wholesale. The study will examine the current market share controlled by G Winery, as well as identifying direct competitors within the wholesale industry. The internal analysis will identify the most profitable products being offered through wholesale as well as determining a target market for wholesale throughout northwest Ohio. The methods include a combination of qualitative and quantitative analysis utilizing primary data from a survey of current wholesale accounts being served by G Winery, paired with extensive market research; the information is used to determine the most successful strategies for business expansion. Furthermore, the study will lay out a job description with key responsibilities for the new Wholesale Account Specialist to focus on securing the market share desired by G Winery.
Keywords: Winery; Wholesale; Market analysis; Agribusiness; Break-even analysis